The body as a mirror of the soul : physiognomy from antiquity to the Renaissance. (Leuven University Press, 2021)
The idea of the body as a mirror of the soul has fascinated mankind throughout history. Being able to see through an individual, and drawing conclusions on their character solely based on a selection of external features, is the subject of physiognomy, and has a long tradition running well into recent times. However, the pre-modern, especially medieval background of this discipline has remained underexplored. The selected case studies in this volume each contribute to a better understanding of the history of physiognomy from antiquity to the Renaissance, and offer discussions on unedited treatises and on the application, development, and reception of this field of knowledge, as well as on visual sources inspired by physiognomic theory.